Digital Media-Based Mathematics Learning Strategies to Enhance Reading Interest Among Elementary School Students - Lastri Lestiawati; Deti Rostini (Journal of Innovation and Research in Primary Education, 2026)
Elementary students' low reading interest significantly impairs their ability to comprehend mathematical word problems, particularly in rural schools with limited technological infrastructure. This study examined how digital media-based mathematics learning strategies enhance reading interest while strengthening numeracy competencies. A qualitative case study was conducted at two Indonesian elementary schools (SDN Puncak 1 and SDN Pasirkampung) using classroom observations, semi-structured interviews with teachers, principals, and students, and document analysis. Data were analyzed following Miles, Huberman, and Saldaña's framework, with triangulation ensuring validity. Systematic implementation incorporating educational videos, interactive e-modules, digital quizzes, and GeoGebra—supported by structured planning, resource organization, and continuous supervision—produced substantial improvements. Student questioning behavior increased 239%, mathematical word problem performance improved from 56.4% to 73.2% (Cohen's d=1.43), and mathematics anxiety decreased from 67% to 38%. Students demonstrated enhanced reading behaviors including spontaneous rereading, text-pointing while reading, and voluntary engagement with mathematical narratives. Digital media-based strategies effectively integrate literacy and numeracy development when supported by systematic management frameworks. Success depends on needs-based planning, teacher professional development emphasizing pedagogical-technological competencies, offline resource preparation mitigating connectivity limitations, and data-driven supervision enabling responsive refinement. Findings validate multimedia learning theory while revealing that resource constraints can generate productive collaborative structures, providing empirical foundations for inclusive digital mathematics education in technologically limited contexts.